A MULTIPLE REGRESSION ANALYSIS OF ECONOMIC OUTPUTS AS A FACTOR IN TIMSS SCORE IN SCIENCE AMONG SELECTED COUNTRIES IN ASIA - Frank Angelo Pacala (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
Trends in International Mathematics and Science Study (TIMMS) is one of the leading organizations that measures the academic competence of students around the world in terms of science and mathematics. This paper studied the idea that high economic output of a country leads to higher average scores TIMMS or vice versa. The independent variables were Gross Domestic Product (GDP) per capita, GDP real, GDP growth, Expenditure on Education, employment rate, and net trade in goods and services while the dependent variable was the TIMMS average score. Using multiple regression analysis (MRA), these independent variables were correlated to the dependent variable while making sure that the assumptions of MRA are observed. It was found out that the economic outputs were not a factor in TIMSS score.